Differentiated Learning Assisted by Angle Meter to Improve Students' Creative Mathematical Thinking Ability on Trigonometry - Yuverni Selvy (Proceeding of International Conference on Multidisciplinary Research, 2024)
Teachers as learning facilitators cannot avoid the diversity of students that occurs in a class, especially in deciding what strategies should be used in learning. As time progresses, today's teachers are required to be innovative, and creative in choosing and developing learning methods. Based on the 2023 Aceh education report card, the numeracy score was below standard, especially in the geometry domain at SMAN 1 Lhokseumawe with a score of 57.84. Numeracy abilities are closely related to creative thinking abilities. Efforts to improve creative thinking abilities mean that teachers must organize learning strategies to meet students' diverse learning needs with differentiated learning. The purpose of writing the paper is to determine the increase in students' mathematical creative thinking abilities with differentiated learning. The indicators of creative mathematical thinking abilities tested are fluency, flexibility, and elaboration. The methodology of this research is descriptive with a sample of class X students at SMAN 1 Lhokseumawe learning trigonometry are elevation and depression in class be concluded that the students' mathematical creative thinking abilities as a group were at 90.375 and individually at 89. The learning process of angle meter-assisted differentiation helps students connect graphical, algebraic, and numerical representations and brings up critical, creative, communicative, and collaborative attitudes in accordance with 21st-century skills.